Feed preference and nutrient digestibility of pelleted or silage form of olive cake as affected by concentrate supplementation - Keles G.; Kocaman V.; Ates S. (Innovation for sustainability in sheep and goats, 2019)
High fiber level of olive cake (OC) is the main limiting factor for its use in animal feeding. Effective industrial-scale destoning process improves its nutritive value but the level of destoned OC (SOC) to be included in the ruminant diets for safe and efficient feeding is yet unclear. Thus, this study was carried out to determine the voluntarily intake of SOC and nutrient digestibility of diet by offering the feed as free-choice. A total of ten, Karya female yearlings were divided into two groups and were fed maize silage-alfalfa hay mix, pellet or silage form of SOC with (Con+) or without concentrate (Con-), as free-choice for 3 weeks. The individual dry matter intake (DMI) was determined for each feedstuff that was offered ad libitum. The difference between two groups (with or without concentrate) was compared by independent t test. The silage-alfalfa mix, SOC silage and pelleted SOC intake of Con- and Con+ yearlings were 778 and 192; 158 and 56 (P<0.001); and 65 and 40 g/kg DM (P =0.06), respectively. The concentrate consumption of Con+ group was 712 g/kg DM. The Con+ yearlings consumed more DM and nutrients, and tended to (P=0.06) grow faster than Con- yearlings. The in vivo apparent DM, organic matter, crude fat, crude protein and non-fiber carbohydrates digestibility were higher in Con+ lambs, while fiber digestibility did not differ (P>0.05) with concentrate supplementation. The results indicated that yearlings had lower preference for SOC as compared to silage-alfalfa mix regardless of the presence of concentrate. The intake of OC was greater in the form of silage than pellet form.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)